KAJIAN PERSEPSI GENERASI Y TERHADAP KETUA: KAJIAN KE ATAS KUMPULAN PENGURUSAN DAN PROFESIONAL DI KEMENTERIAN PEMBANGUNAN WANITA, KELUARGA DAN MASYARAKAT (KPWKM) DAN AGENSI - Bakar, Al-Azmi; Idris, Maarof; Munusamy, Gunaseelan (Journal of Techno-Social, 2016)
Generation Y which also known as Millennium Generation are a cluster of generation often get convergence for the characters like think out of the box, freedom of expression, high in technological literacy (IT Savvy) and so on. This study aimed to get the perception of Management and Professional Group (M & P) officers from Generation Y towards their superiors. This study is important to know and analyze M & P Group Officers perception from generation Y towards their respective superiors to break up differences and reduce the gap between them that affects productivity and leadership in the organization. The gap in terms of work between these two (2) timely framed generations ‘people is identified throughout this research to create cooperation and reduce differences. The findings obtained by using a specially designed questionnaire which is used to determine the perception and expectations of the M& P Group officers to their superiors. The findings showed that the majority of respondents (M& P Group officers) agreed that their superiors showing realistic work, cheerful and in accordance with the latest technology. They are of the opinion that the superiors have skills using the latest technology in managing the implementation of daily work processes and transmission of important information to their subordinate. The Group was also satisfied with the treatment given to them and their welfare also taken care by their superiors. This questionnaire also analyzed the characteristics of respondents which are significant with the characteristics shown by Generation Y people such as need of freedom in performing a work, requires recognition of the view and the tasks performed, wanting fair and open minded superiors, keeping the welfare of the employees, and superiors have to make firm decision and give clear instructions in the matters pertaining to important job.